2003
DOI: 10.1063/1.1557308
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic core loss of ultrahigh strength FeCo alloys

Abstract: Hiperco® 50 alloy heat treated between 450 and 650 °C exhibits superior mechanical properties. We report the measurements of the ac core loss at various frequencies up to 4500 Hz of the Hiperco® 50 alloy samples annealed at 450 and 650 °C. The 650 °C annealed specimens have lower ac core loss than that of the 450 °C annealed ones. The total core loss, consisting of contributions from hysteresis core loss and eddy-current core loss, depends on frequency f as af+bf2. The eddy-current loss of a single laminate is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 8 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…1), it is found that r ¼ 580 MPa, which is quite close to the yield value. 18 As expected for a beam under high tensile stress, halving the length of the bridge to 0.5 mm led to a resonance frequency of approximately twice (256 kHz), which was confirmed by the fact that the frequency component was present in the FFT at all locations (Positions 2-6, Fig. 2(b)) along the length of the bridge but not on the substrate.…”
supporting
confidence: 70%
“…1), it is found that r ¼ 580 MPa, which is quite close to the yield value. 18 As expected for a beam under high tensile stress, halving the length of the bridge to 0.5 mm led to a resonance frequency of approximately twice (256 kHz), which was confirmed by the fact that the frequency component was present in the FFT at all locations (Positions 2-6, Fig. 2(b)) along the length of the bridge but not on the substrate.…”
supporting
confidence: 70%
“…Recent developments have confirmed and exploited (for example [62]) the possibility for these alloys to recrystallise at low temperature. Buckley [63,64] investigated the interactions between the ordering reaction and recrystallisation.…”
Section: Recrystallisation and Grain Growthmentioning
confidence: 93%
“…The evolution Table 7 The difference (DH c ) between observed coercivity and that predicted from the grain size using Eq. (10) as a function of the volume fraction (V f ) of second phase Alloy (addition in wt%) of magnetic and electrical properties during ageing is a recent concern and few studies have been undertaken [31,35,62,71]. These are discussed in greater detail later.…”
Section: Precipitationmentioning
confidence: 97%
“…36,98 Further, these nanocrystalline alloys exhibit at least 3% room temperature ductility in the ordered condition and only a moderate decrease in yield strength up to 400uC. Cheng et al 230 reported the AC core loss of these bulk nanocrystalline alloys at various frequencies up to 4500 kHz. The core loss of the alloy is found to decrease with decreasing frequency and increasing grain size.…”
Section: Nanocrystalline Alloys Produced By Primary Crystallisation O...mentioning
confidence: 99%